The relationship between financial development and international trade in Turkey - Ertuğrul, Kerime Aycan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This thesis examines the short-run and long-run relationships between financial development and international trade in Turkey from the first quarter of 1990 to the second quarter of 2017. Initially, two supply-leading hypotheses which imply that financial development causes economic growth and international trade are investigated. Then, three demand-following hypotheses which imply that the economic growth and international trade cause financial development are analyzed. In the hypotheses, international trade indicator is defined as the sum of imports and exports; while financial development indicators are defined as the money supply M2 as a proxy for the breadth, the banking system’s credit to the private sector as a proxy for the depth and the stock market capitalization as a proxy for the liquidity of the financial development. Johansen’s Cointegration Test and Vector Error Correction Model are applied for investigating the long run and short run causations, respectively. According to the results of the econometric analyses, there are bi-directional long-run causation between private sector credits and real economic growth as well as stock market capitalization and trade openness. Also, in the long-run, there are positive causations from international trade to M2 money supply and from M2 money supply to real economic growth. On the other hand, it is found that there is short-term causation from stock market capitalization to the real economic growth.
Keywords: Financial economy -- Turkey.; International trade -- Finance.